Quantum control in size selected semiconductor quantum dot thin films - Kärcher Victor; Reiker Tobias; da Costa Pedro F.G.M.; de Camargo Andrea S.S.; Zacharias Helmut (Nanophotonics)
We introduce a novel technique for coherent control that employs resonant internally generated fields in CdTe quantum dot (QD) thin films at the L-point. The bulk band gap of CdTe at the L-point amounts to 3.6 eV, with the transition marked by strong Coulomb coupling. Third harmonic generation (λ 3 = 343 nm, hν = 3.61 eV) for a fundamental wavelength of λ 1 = 1,030 nm is used to control quantum interference of three-photon resonant paths between the valence and conduction bands. Different thicknesses of the CdTe QDs are used to manipulate the phase relationship between the external fundamental and the internally generated third harmonic, resulting in either suppression or strong enhancement of the resonant third harmonic, while the nonresonant components remain nearly constant. This development could pave the way for new quantum interference–based applications in ultrafast switching of nanophotonic devices.